Why Do Things Move People?: The Jerusalem Temple as Emotional Repository - Barton, Stephen C. (Journal for the study of the New Testament, 2015)
This article brings social-scientiﬁc method to bear on a biblical subject by asking the Durkheimian question, ‘Why do things move people?’, and asking it in relation to the Jerusalem temple. More speciﬁcally, drawing upon anthropological study of the emotions, an apparently neglected aspect of temple studies is opened up, namely, whether or not, and if so how, the power of the temple to ‘move’ people arose in part at least from its function as an emotional repository, the latter understood as consisting of material objects, persons, beliefs and practices that, in a highly concentrated way, constitute a ‘place’ where a people’s sense of identity, value and order are focused. At relevant points, implications for interpreting the affective aspect of New Testament ‘temple’ texts are offered.